The factors that cause companies to be suspended from the Kuala Lumpur stock exchange / Mohd Hassan Che Haat … [et al.] - Che Haat, Mohd Hassan; Abd Rahman, Rashidah; Abd Hamid, Nadiah; Mahenthiran, Sakthi (Faculty of Accountancy & Accounting Research Institute (ARI), 2006)
This is an empirical study of troubled (i.e., PN 4) companies, and their agency costs to outsiders who invest in them. The sample consisted of 21 companies each in three groups made up ofPN4, positive economic profit and negative economic profit companies. The study finds that outside investors in PN 4 companies incurred extreme agency costs compared to positive economic profit companies because of poor governance. Relative to the control group, PN 4 companies had higher insider ownership, borrowing, and lower equity values. The study highlights the uniqueness of the Malaysian securities law that allows corporate insiders to proactively use monitoring mechanisms to lower agency costs.